Особенности методики эндовенозной лазерной коагуляции и foam-form склеротерапии при лечении хронического заболевания вен класса С2 - Кузьменко, О.В.; Михайличенко, В.Ю. (Актуальні проблеми транспортної медицини, 2014)
Применение комбинированных малоинвазивных методик лечения варикозной
болезни нижних конечностей, на данный момент времени почти полностью вытеснили традиционные оперативные вмешательства. В основу работы лежит анализ лечения 384 пациентов с заболеванием вен нижних конечностей С2 (по классификации
СЕАР), которые находились на стационарном лечении. Пациенты были разделены
на 5 групп: 1 группа контрольная (№80) – пациентам была выполнена стандартная
флебэктомия и 4 групп – группы сравнения: 1а – пациентам выполнено эндовазальная лазерная коагуляция (ЭВЛК) — №62; 1в – склеротерапия (СТ) — №57; 1с –
ЭВЛК+СТ (№45); 1d – ЭВЛК+СТ+подкожное пересечение вен или минифлебэктомия
(№140). При сравнении всех побочных эффектов и осложнений, мы видим, что по
большинству изучаемым параметрам (послеоперационные осложнения, побочные
эффекты и качество жизни пациентов), наихудшие результаты получены в контрольной группе, т.е. больным которым выполняли традиционную флебэктомию. Суммарно наилучшие результаты получены в группе 1d. Нами применен дифференцированная лечебная тактика при комбинированном лечении, так до верхней трети
голени и бедре мы используем ЭВЛК, ниже СТ, что позволило полностью избежать
невритов подкожных чувствительных нервов на голени. Применение радиарного, а
не торцевого лазера на бедре при диаметре вены более 1,3 см, позволило добиться
в 100 % полной облитерации сосудов. Ограниченные тромбофлебиты в группе контроля, составили 5 %, преходящие парестезии 22,5 %, подкожные гематомы 30 %,
образование сером и/или нагноение в 27,5 %. По всем параметрам, число осложнений было в 4-5 раз выше, чем в подгруппах с малоинвазивными методиками, что
еще раз подчеркивает большую травматизацию тканей при данной методике.
Отмечено, что малоинвазивные технологии имеют ряд преимуществ перед традиционным видом хирургического лечения ХЗВ, в виде снижения количества осложнений и побочных эффектов, а также значительном повышении качества жизни пациентов с данным видом патологии. Застосування комбінованих малоінвазивних методик лікування варикозної
хвороби нижніх кінцівок, на даний момент часу майже повністю витиснули
традиційні оперативні втручання. В основу роботи лежить аналіз лікування 384
пацієнтів із захворюванням вен нижніх
кінцівок С2 (по класифікації СЕАР), які
перебували на стаціонарнім лікуванні.
Пацієнти були розділені на 5 груп: 1 група контрольна (№ 80) – пацієнтам була
виконана стандартна флебектомія й 4 груп – групи порівняння: 1а – пацієнтам
виконане ендовазальна лазерна коагуляція (ЕВЛК) — № 62; 1в – склеротерапія
(СТ) — № 57; 1з – ЕВЛК+СТ (№ 45); 1d
– ЕВЛК+СТ+підшкірне перетинання вен
або мініфлебектомія (№ 140). Нами застосований диференційована лікувальна
тактика при комбінованім лікуванні, так
до верхньої третини гомілки й стегні ми
використовуємо ЕВЛК, нижче СТ, що дозволило повністю уникнути невритів
підшкірних чутливих нервів на гомілці.
Застосування радіарного, а не торцевого лазера на стегні при діаметрі вени
більш 1,3 див, дозволило добитися в 100
% повній облітерації судин. При порівнянні всіх побічних ефектів і ускладнень, ми бачимо, що по більшості досліджуваним параметрам, найгірші результати отримані в контрольній групі, тобто
хворим яким виконували традиційну флебектомію. Сумарно найкращі результати
отримано в групі 1d. Обмежені тромбофлебіти в групі контролю, склали 5 %,
минущі парестезії 22,5 %, підшкірні гематоми 30 %, утвір сірому й/або нагноєння в 27,5 %. По всіх параметрах, число
ускладнень було в 4-5 раз вище, чим у
підгрупах з малоінвазівними методиками, що ще раз підкреслює більшу травматизацію тканин при даній методиці.
Відзначене, що малоінвазивні технології мають ряд переваг перед традиційним видом хірургічного лікування ХЗВ,
у вигляді зниження кількості ускладнень
і побічних ефектів, а також значнім підвищенні якості життя пацієнтів з даним видом патології. The main purpose of contemporary phlebology is to transform the operative
surgery procedure in the “one-day
surgery” by maintenance of maximal
cosmetic effect and absence of relapse as
well as post-operative complications.
Purpose is in the comparative
assessment of traditional and small invasive
treatment methods of С2 chronic vein
disease on the basement of analysis of
operative interference complications and
postoperative results.
Material and methods. In the study
basement are investigation and treatment
data of 384 patients with С2 low extremities
vein disease (according to the СЕАР
classification) that were on the stationary
treatment in the department of Urgent and
Recovery Vascular Surgery of SI “Institute
of Urgent and Recovery Surgery n.a. V.K.
Gusak of NAMS of Ukraine” (Donetsk) from
2009 till 2012. We divided the patients into
five groups: in the 1 control group
(consisted of 80 patients) took place the
standard phlebectomy; the other 4
comparison groups went trough the
following: in the 1а group was implemented
endovasal laser coagulation (EVLC); and
this group consisted of 62 patients; the 1в
group went through the sclerotherapy (ST)
and included 57 patients; the 1с group had
EVLC+ST (it numbered 45 patients); 1d
group went through the
EVLC+ST+subcutaneous vein intersection
or mini-phlebectomy (this group included
140 patients). The middle age of patients
was 25,8 ± 7,2. In the control group took
place classic phlebectomy. For EVLC we
used a universal laser coagulator Lika-Surgeon by “PhotonicaPlus” with the wave
length of 1470 nm. The surgery as a rule
was added by the mini-phlebectomy stage
by Muller or by foam-form
echosclerotherapy.
For the effectiveness investigation of
the mentioned treatment procedures took
place general assessment of quality of life
in patients with the help of CIVIQ
questionnaire before the surgery and 1
year after the surgical treatment.
Results and their discussion. The
most common complication were limited
thrombophlebitises that consisted 10,2
%; the second one by the frequency were
subcutaneous hematomas with 6,9 %; and
after that went down transient paresthesias
with 4,9 %; and seromas and/or wound
suppuration appearance that was 4,3 %.
The limited thrombophlebitises in the
control group numbered 5 %; transient
paresthesias were 22,5 %; subcutaneous
hematomas consisted 30 %; seromas and/
or wound suppuration appearance
numbered 27,5 %. According to the whole
parameters the complication number was
4-5 times higher than in the sub-groups
with small invasive methods that once more
underlines the great tissue traumatization
by the using of this method.
The most numerous number of
complications were ecchymoses; they
numbered 38,8 %; bands were observed in
31,25 % of cases and skin pigmentation
was fixed in 7,2 % of cases. It should be
noticed that EVLC was characterized by the
ecchymoses and pigmentations but for the
ST it was band appearance.
We used differential treatment
practice in combined therapy; thus we
apply EVLC to the upper third of shin and
hip; for the lower parts we use СТ, which
allowed absolutely avoiding the development of neuritis of subcutaneous
sensible nerves on the shin. The
implementation of radiar but not frontal
laser on the hip with vein diameter more
than 1,3 cm; it permitted to achieve the 100
% absolute vessel obliteration.
Thus in comparison of all these side
effects and complications we see that by
the majority of the studied parameters the
worthiest results were achieved in the
control group; videlicet, with the patients
that went through the traditional
phlebectomy. In total the best results were
achieved in the 1d group. The small invasive
technologies during the CVD treatment
increase the quality of life on the 26,8
points and traditional one on 17,4 points.
Conclusions. As a result of the
fulfilled comparative analysis we showed
that small invasive technologies had a
number of advantages over the traditional
surgical treatment methods in CHD, such
as decrease of the complications number
and side effects as well as in the substantial
increase of patients’ quality of life with the
mentioned pathology.